The typology of religious extremism - Rixer, Ádám (Advances in Social Sciences Research Journal, 2019)
Abstract Although the contemporary scholarly literature that addresses extreme religious phenomena is very rich, no comprehensive systematisation of religious extremism has been put forward, and neither is there an exhaustive typology for this issue. Using Hungary as a model, this paper will suggest a systematic scheme that can also be adapted to other states, looking at three aspects of religious extremism – 1) whether the norms that are accepted by the majority of the society and are violated by the extremist activity are legal norms or non-legal social norms; 2) whether the “extreme” behaviour has a negative impact on the community outside the religious group, or the negative impact predominantly affects the religious group itself; 3) whether or not it involves violence – and based on these, will differentiate between seven types of extremism. The focus here is on a legal analysis, but the cases cited and conclusions inferred go far beyond legal norms and resolutions.